PEMETAAN KANTOR POLISI KABUPATEN SITUBONDO BERBASIS PETA - Ahmad Rofiqi (Department of Science and Technology Ibrahimy University, 2018)
Situbondo Regional Police are law enforcers who work in the East Java Situbondo district. Of course, in carrying out all its duties, it requires communication and information exchange between officers and civilians to carry out police duties properly and effectively. In reality on the ground, not all Situbondo people, especially those outside Situbondo, know the geographical location of the police station in each sub-district in Situbondo district. The only way to find the Situbondo Police Station is to ask and ask someone who has visited or learned about the office. However, using this procedure requires more time and is a bit of a hassle for other people, this is due to the absence of a map pointer to deliver or give an overview of the location of the Police station. From the above problems, namely the absence of loyal Police station appointees at all times to help, it is necessary to design a Situbondo Police Station Geographical Information System that is the answer to the problems discussed above. The establishment of this system is expected to be able to assist the Police in informing the geographical location of the Police station along with important information and also assisting the public in finding the Police station quickly and effectively.